A comprehensive review of polyethylene pipes: Failure mechanisms, performance models, inspection methods, and repair solutions - Wang, Hao; Shah, Jay; Hawwat, Said-El; Huang, Qindan; Khatami, Alireza (Journal of Pipeline Science and Engineering, 2024)
•Polyethylene (PE) pipes account for up to 90–95 % of new gas distribution pipelines in Europe and the United States.•The failure of a PE pipe is a multivariate problem that can occur due to pre-existing defect growth, material aging, or foundation settlement.•Long-term hydrostatic strength test results are extrapolated to predict the lifetime performance of the pipeline; however, this method does not account for the effects of material aging.•The use of ultrasonic testing is highly restricted to the welded sections of PE pipes, relative to its versatile usage in inspecting steel pipes.•PE demonstrates poor adhesion properties due to its low surface energy, making it challenging to develop adhesion-based repair techniques for incipient surface defects. Polyethylene (PE) pipes are widely used for natural gas distribution due to their good durability and low costs. To ensure the integrity of PE pipelines, it is crucial to develop a comprehensive understanding of pipe failure mechanisms and to recognize the benefits and limitations of different pipeline monitoring strategies. This review provides an overview of different types of pipe failures in the context of their response to operational loads and material degradation. It also covers the details of mechanical tests for predicting the long-term performance of pipes, theoretical models for studying defect growth, examines different defect detection methods, and concludes with an assessment of pipe repair techniques. The findings highlight the importance of investigating the effects of existing defects on the operational performance of the pipeline. This indirectly emphasizes the need to develop time- and cost-efficient strategies to detect defects in the early stages. There is a clear gap in the inclusion of PE aging effects in the lifetime performance models. In addition, given the large number of inspection techniques, a regulated selection of pipeline inspection methods is highly desired, specific to the defect type. Further research in advancing adhesive-based repair of incipient defects is crucial to prevent catastrophic defect growth. [Display omitted]